1999
DOI: 10.1016/s0005-2736(99)00037-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequencing of the cDNA for vacuolar H+-pyrophosphatase from Chara corallina

Abstract: We have cloned a cDNA for vacuolar proton-translocating pyrophosphatase of Chara corallina that is one of the closest green algae to the land plants. The deduced protein consists of 793 amino acid residues. Its sequence is 71% identical to the H+-pyrophosphatases of land plants, and is less than 46% identical to those of marine alga and phototrophic bacterium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This was supported by immunochemical study with an antibody specific to this sequence (DVGADLVGKVE) (12). This sequence is common among VPPases not only from land plants but also from Chara corallina (10), Acetabularia acetabulum (13), R. rubrum (5), Thermotoga maritima (GenBank™ accession number AE001702), and P. aerophilum (6). Studies using substrate analogs, such as aminomethylenebisphosphonate, have also provided information on the catalytic domain (14 -16).…”
Section: Vacuolar Hmentioning
confidence: 94%
See 2 more Smart Citations
“…This was supported by immunochemical study with an antibody specific to this sequence (DVGADLVGKVE) (12). This sequence is common among VPPases not only from land plants but also from Chara corallina (10), Acetabularia acetabulum (13), R. rubrum (5), Thermotoga maritima (GenBank™ accession number AE001702), and P. aerophilum (6). Studies using substrate analogs, such as aminomethylenebisphosphonate, have also provided information on the catalytic domain (14 -16).…”
Section: Vacuolar Hmentioning
confidence: 94%
“…Thus, V-PPase should have a specific binding site for its substrate (Mg-PP i ), Mg 2ϩ , K ϩ , and Ca 2ϩ in addition to a H ϩ transport channel. Multiple amino acid sequence alignment of V-PPases of various organisms revealed highly conserved regions (2,3,10). There is a putative substrate-binding motif of DXXXXXXXKXE in the cytoplasmic loop (1,11).…”
Section: Vacuolar Hmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental system clearly needs revisiting. Nakanishi et al (1999) found the cDNA sequence of the C. corallina PPase 71% identical to that of land plants and 46% identical to that of chlorophyte Acetabularia and phototropic bacterium Rhodospirillum rubrum .…”
Section: One Plant – Many Experimental Systemsmentioning
confidence: 94%
“…33 The protein topologies were predicted using MEMSAT-SVM prediction, 34 TMHMM prediction 35 and TMpred server. 36 The MEMSAT algorithm employed empirically derived topological data, from available membrane proteins. All residues were assigned to one of five states (inner helix end, middle helix, outer helix end, intracellular, and extracellular).…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%